2009
DOI: 10.4102/sajip.v35i1.730
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress, ill health and organisational commitment of employees at a university of technology

Abstract: The aim of this study was to investigate the relationship between occupational stress, ill health and organisational commitment. A survey design was used. The sample (N=353) consisted of academic (n=132) and support staff (n=221) at a university of technology. The Organizational Stress Screening Tool (ASSET) and a biographical questionnaire were administered. The results showed that different organisational stressors contributed signifi cantly to ill health and low organisational commitment. Stress about job s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 40 publications
3
42
0
2
Order By: Relevance
“…Overload, control, aspects of the job, and pay and benefits lead to low individual commitment of employees in a technology university [3]. Also, anxiety influences career commitment significantly [17].…”
Section: Stressor and Commitmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Overload, control, aspects of the job, and pay and benefits lead to low individual commitment of employees in a technology university [3]. Also, anxiety influences career commitment significantly [17].…”
Section: Stressor and Commitmentmentioning
confidence: 99%
“…A number of studies have shown that stress affects negatively the perceived commitment of the organization to the employee. A number of stressors such as control and resources and communications influence low organizational commitment [3]. Meanwhile, individual commitment refers to how employees are committed to their organizations.…”
Section: Stressor and Commitmentmentioning
confidence: 99%
See 3 more Smart Citations